Analisis Preferensi Pengguna Terhadap Sistem Transportasi Online Di Kota Sorong - Rahayu Erwi Yani Putri; Musvira Febriana Umar; Andi Rahmat (BULLET : Jurnal Multidisiplin Ilmu, 2025)
This study aims to analyze user preferences toward online transportation systems in Sorong City. Along with the development of digital technology, online transportation services such as Maxim, Gojek, and Grab are increasingly favored by the public due to their convenience, speed, and comfort. However, user satisfaction and preferences can be influenced by various factors, such as price, safety, comfort, speed, accessibility, and application features. This research was conducted using a quantitative method with a descriptive approach. The data were collected through questionnaires distributed to 100 respondents who are active users of online transportation services in Sorong City. The analytical technique used is conjoint analysis to determine the most preferred service attributes and combinations by users. The results show that application features are the most influential factor in user preferences, followed by speed, price, accessibility, comfort, and safety. These findings indicate that online transportation service providers should focus on enhancing user-friendly application features and improving speed to increase customer satisfaction and loyalty. This study is expected to serve as input for both service providers and local governments in formulating transportation policies based on community needs.